The role of sport events in improving regional community welfare: a case study in sukabumi city - Ganjar Ramdani Saputra; Indra Wiguna (Universitas Suryakancana, 2025)
Sports have become an important aspect of people's lives, not only as a means to maintain health, but also as a tool to improve people's economic welfare. This study aims to analyze the role of sports events in improving people's welfare in Sukabumi City. Through a qualitative approach and secondary data analysis, this study found that sports events can encourage local economic growth, increase community participation, and strengthen social solidarity. The data shows that sports events held in Sukabumi are able to attract visitors from outside the region, which has a positive impact on the MSME and tourism sectors. Sports events have an important role in improving people's welfare in the region, especially in the context of Sukabumi City. This study is expected to provide insight for stakeholders in planning and implementing more effective sports events. This study aims to analyze the impact of organizing sports events on the local economy, community participation, and improving the quality of life. The results of the study show that sports events not only increase local economic income, but also strengthen communities and improve public health. Thus, sports events can be used as an effective strategy in efforts to improve people's welfare.